Los índices bursátiles de sostenibilidad en América Latina y el Caribe: relevamiento empírico (2022)
This paper aims to know the presence of sustainable indices in the Latin American context and analyze them from the point of view of their methodology, operation and purpose. The Latin American stock exchanges listed as members of the United Nations Sustainable Stock Exchanges initiative as of November 2020 and the information available in the methodological guides of each index were considered for the study. From the analyzes carried out, it can be seen that Europe and Asia are the markets with the highest number of active indices and that their presence in Latin America and the Caribbean is low and incipient. Regarding the methodologies of each index, it can be seen that they vary according to the index being considered. Although the joint presence of best in class criteria and exclusion criteria is observed, they differ in terms of the sustainability analysis they make for each dimension, which is not general but, on the contrary, specific.